THE USE OF DIGITAL EDUCATIONAL TECHNOLOGIES IN LINGUODIDACTICS (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
Article is devoted to the study of the use of digital educational technologies in linguodidactics. The paper examines the theoretical foundations of linguodidactics and the features of applying digital technologies in language learning. Special attention is given to types of digital educational technologies, including online platforms, multimedia resources, mobile applications, and interactive tools, as well as their impact on the effectiveness of the educational process. The study analyzes the advantages of using digital technologies, such as increasing students’ motivation, developing independence, and individualizing learning. The work demonstrates that the integration of digital educational technologies contributes to modernizing teaching methods and improving the quality of the educational process.